2017
DOI: 10.1093/her/cyx058
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cultural norms and roles in the use and abuse of alcohol among members of a rural community in Southeast Nigeria

Abstract: Social influences together with local cultural norms are central factors that can influence the use of alcohol. The study, therefore, identified socio-cultural norms and roles capable of influencing alcohol use among young people in an alcohol producing community, in Nigeria. We used qualitative technique - focused group discussions among selected key persons in the area of study. Three groups; adult males, adult females and youths were engaged in discussions around the themes of socio-cultural; norms, roles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Table 2 show that t statistic is 0.47, which is below the values of different significance levels. Therefore, it can be concluded that the research results of college students' employability are stable and the results are highly credible (Nwagu et al, 2017;Akre, Suris, 2017).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 85%
“…Table 2 show that t statistic is 0.47, which is below the values of different significance levels. Therefore, it can be concluded that the research results of college students' employability are stable and the results are highly credible (Nwagu et al, 2017;Akre, Suris, 2017).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 85%
“…Second is the survey of evaluation indicators of school form students and teachers. Third is the survey of corporation model between enterprises and universities (Nwagu et al, 2017;Hardy and Totman, 2017). This paper firstly adopted questionnaire survey method to have research on 500 current university students, the composition of universities is academic application (23%), engineering application type (24%), technical application type (20%), skill application type (33%), as shown in Table 2 (Hao et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to the management methods of credit system in universities, the credit of practice teaching should be 20% of the total credits, and a perfect practice teaching evaluation system should be formulated. The Evaluation system of practice teaching is shown as Table 1 (LaChausse, 2017;Nwagu et al, 2017).…”
Section: Resultsmentioning
confidence: 99%